EMPLOYEE ENGAGEMENT IN REMOTE WORK SETTING STRATEGIES FOR HR TO FOSTER MOTIVATION AND COMMITMENT - Beenish Ahmed; Shahrukh Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This study delves into the complexities of employee engagement within remote work environments in Pakistan. By examining the experiences of 25 diverse participants across various industries in Pakistan, we sought to uncover strategies that optimize both productivity and employee well-being outside the traditional office setting. Through in-depth interviews and rigorous thematic analysis, three core themes emerged: communication dynamics, work-life balance, and organizational support. HR practices in Pakistan that emphasize open and frequent communication are essential for effective remote work, clear boundaries between work and personal life, and a supportive organizational culture. This research underscores the importance of tailored communication strategies, professional development opportunities, and a strong emphasis on employee well-being in fostering a thriving remote workforce in Pakistan. Keywords: Remote work, employee engagement, work-life balance, communication, organizational support, Pakistan.